Legal Review Of The Judge's Decision On Perpetrators Of Narcotic Crimes Of The Meth Type Below The Minimum Limit Of Criminal Sentence (Study Of Supreme Court Decision Number 3061k/Pid.Sus/2024) - Sinaga, Rahmah Hayati; Rahmayanti (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The imposition of sentences below the minimum sentence limit in narcotics cases is a serious problem in criminal law enforcement in Indonesia. This study aims to analyze the causes of disparities in judges' decisions in narcotics cases, examine the provisions for imposing sentences below the minimum sentence limit, and explore the basis for judges' considerations in Supreme Court Decision Number 3061K/Pid.Sus/2024. This study uses a normative juridical approach with decision analysis as a case study. The results show that judges' freedom to interpret the law can result in decisions that deviate from the minimum sentence stipulated by law, which ultimately can create legal uncertainty and reduce the deterrent effect in narcotics law enforcement.